Predictive processing can override perceptual information: evidence from Spanish object relative clauses - Sara Fernández Santos; Miquel Llompart; Ewa Dąbrowska (Language and Cognition)
This study examines the role of the timing of obligatory disambiguating information – obligatory cues – and presence/absence of optional morphological markers in resolving temporary syntactic ambiguity in Spanish object relative clauses. Native adult comprehension (Study 1) reveals similar accuracy for clauses with relatively early obligatory cues, regardless of the presence/absence of additional markers, and those with late obligatory cues with additional markers, but reduced accuracy for those with late obligatory cues without additional markers. Given the phonetic resemblance of the late-disambiguated variant with its corresponding subject relative, we conduct two follow-up perceptual identification tasks with the whole relative clause, including the head (Study 2), and relative clause fragments (Study 3). The identification tasks show that, when instructed to attend to the form of the structures, participants perceive acoustic differences but retain a bias towards subject-relative interpretations. Our results suggest that additional markers aid comprehension of non-canonical structures when obligatory cues occur relatively late within the structure and highlight the dominance of predictive processing over perceptual information in such cases of late disambiguation.